Mechanochemical Process in the TiO2-Al-C Mixture to produce Al2O3-TiC - Fatemeh Homayooni; Nader Setoudeh; Abbas Mohassel; Fatemeh Heidari; Mohammad Sajjadnejad (شیمی کاربردی روز)
The mixture of TiO2-Al-C with stoichiometric ratio was prepared then ball milling process was done in a planetary ball mill in different times. The evidence of a chemical reaction was not detected in the 1 h milled sample however, the sign of an exothermic peak was detected at ~690ºC in the DTA results for this mixture. The XRD results of the as-milled samples indicated that the chemical reaction progresses as MSR model in the mixture with stoichiometric ratio. The decreasing of the particles size and the traces of amorphization were observed after increasing the milling time to 7 hours. The products of rection (i.e., Al2O3 and TiC) were well crystallized after isothermal heating of the 5 h milled sample at 1000 ºC for 1 h under argon atmosphere. The signs of these phases were also observed in the XRD patterns of the solid residues after DTA analysis. The evolution of the microstructures indicated the decreasing in the particle size due to ball milling and the change of morphology of the microstructure due to occurrence of chemical reaction. The assessments of the lattice parameter of the TiC in the final products indicated that the lattice parameter changes and reaches to amount of the stoichiometric composition due to isothermal heating. Thermodynamics assessments were done for the mixture of TiO2-Al-C and the feasibility of the reactions was studied using HSC thermodynamics software. The XRD results of the milled and the isothermally heated samples were accordance with the thermodynamics assessments.